2017
DOI: 10.4103/jehp.jehp_142_14
|View full text |Cite
|
Sign up to set email alerts
|

Altruism, the values dimension of caring self-efficacy concept in Iranian pediatric nurses

Abstract: Background:Self-efficacy is the most influential among factors affecting nurses’ performance. Yet, understanding of the constituent elements of the caring self-efficacy concept was not considered. This study was to introduce altruism as one of the main aspects of caring self-efficacy in pediatric nurses.Materials and Methods:This is part of a larger study on the concept of caring self-efficacy conducted with qualitative content analysis approach in Iran. Participants included 27 clinical pediatric nurses and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…Cheng et al [32] reported that the higher the self-efficacy perceived by pediatric nurses, the higher the professional perception, and the better the relationship between nurses and patients. Alavie et al [26], in their analysis of the concept of pediatric nurses' care self-efficacy, highlighted the importance of the provision of sufficient explanations to hospitalized children and their families, which improves the self-efficacy of child care to such a degree that FCC is fully implemented. Based on these previous findings, the result in this study could be explained as follows: nursing professional self-efficacy in pediatric nurses affected their attitude toward the importance of the patient's family and nurse-parent partnership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al [32] reported that the higher the self-efficacy perceived by pediatric nurses, the higher the professional perception, and the better the relationship between nurses and patients. Alavie et al [26], in their analysis of the concept of pediatric nurses' care self-efficacy, highlighted the importance of the provision of sufficient explanations to hospitalized children and their families, which improves the self-efficacy of child care to such a degree that FCC is fully implemented. Based on these previous findings, the result in this study could be explained as follows: nursing professional self-efficacy in pediatric nurses affected their attitude toward the importance of the patient's family and nurse-parent partnership.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that the nurse's experience [14], nurse-parent partnership [8,13,14], attitudes to families' importance in nursing care [3,5,20], and nursing professional self-efficacy [2,26,27] affect the quality of nursing in hospitalized children. Based on the literature review, a hypothetical model of this study was constructed.…”
Section: Hypothetical Modelmentioning
confidence: 97%
“…To develop emotional selfregulation skills, they must not become stressed and should have self-control so that they are not distressed with apprehension (Bandura, 2010). Self-efficacy is a dominant issue in defining how an individual performs, thinks, and reacts in case of challenging circumstances (Alavi et al, 2017;Downes et al, 2017). Self-efficacy is crucial in evolving learners' behavior to simplify their learning progression (Fan and Williams, 2010;Roddenberry and Renk, 2010;Van Dinther et al, 2011).…”
Section: Self-efficacymentioning
confidence: 99%
“…The selection and sequencing of learning material are criticised in this study for its reliance on anecdotal evidence or on the intuition of the language teacher, which evidentially is often wide off the mark when compared to corpus data. It is the argument in this chapter that the use of corpus data provides the language teacher with guidance on both macro-and micro-level with regard to the content of the curriculum (Taljard 2012).…”
Section: Corpora For Language Teachingmentioning
confidence: 99%